Petrology, geochemistry, and U-Pb (zircon) age of the quartz-feldspar porphyry dyke at the Lake George antimony mine, New Brunswick: implications for origin, emplacement process, and mineralization - Leonard, P.; Lentz, D.; Poujol, M. (Atlantic Geology, 2006)
ABSTRACT A steeply west-dipping, north-northwest-trending, biotite-bearing quartz-feldspar porphyry dyke is associated with the Lake George granodiorite, a cupola of the Pokiok Batholith. These Early Devonian intrusions are spatially and temporally related to W-Mo-Au and Sb-Au mineralization in the area. The porphyry dyke yielded an age of 420.8 +5.9/-4.0 Ma (U-Pb zircon) and is inferred to be coeval with or slightly older than the Lake George granodiorite (412 +5/-4 Ma, U-Pb zircon). The variably altered dyke contains subhedral to anhedral (rounded) quartz, plagioclase, and orthoclase phenocrysts (0.5 to 30 mm; 30 to 60 vol. %), and numerous angular to subrounded xenoliths of altered intrusion carapace and quenched dyke rocks, as well as local Kingsclear Formation metasedimentary rocks. The dyke is similar to the Lake George granodiorite in phenocryst population, volcanic arc (I-type) afﬁnity, average Zr (157 ppm), TiO2 (0.54 %), La/Yb ratio (13), and REE (129 ppm). The average Au content is lower in the dyke (20 ppb) than in the granodiorite (32 ppb), the abundance of gold is related to minor magmatic hydrothermal chalcopyrite and pyrrhotite (< 2 %). Based on textural evidence, including autobrecciation, coupled with rheological and thermal modeling calculations for the 5 m-wide dyke, it is suggested that ﬂuidization (vapour exsolution) of the magma was key to its rapid emplacement as a quenched glass-gas mixture (tufﬁsite). The S abundance and S isotopic signature of the dyke, relative to Au and Cu abundance, support reduced I-type magmatic volatiles involved in dyke emplacement and cogenetic autometasomatic alteration.